The Effectiveness of Lavender Aromatherapy in Improving Sleep Quality in Hemodialysis Patients : A Literature Review - Liana Veranika; Nurina Aulia Hanun; Fahrun Nur Rosyid; Puji Kristini (International Journal of Health and Social Behavior, 2025)
Chronic Kidney Disease (CKD) is a condition caused by structural or functional abnormalities characterized by a decrease in the glomerular filtration rate (GFR). One of the treatments for CKD patients is hemodialysis (HD). Sleep disorders are among the complications of hemodialysis. Administering lavender aromatherapy is a method to improve the sleep quality of patients. This study uses a literature review method. Articles were searched on ScienceDirect, PubMed, and Google Scholar using advanced search with the keywords "Chronic Kidney Disease, Hemodialysis, Lavender Aromatherapy," resulting in 10 relevant articles to compile this review. The results showed that lavender aromatherapy was effective in addressing complications such as poor sleep quality, fatigue, pain, and anxiety in hemodialysis patients. In conclusion, lavender aromatherapy has been proven effective in improving the sleep quality of HD patients.